Korupsi, Kemiskinan dan Masalah di Negara Berkembang - Sukawarsini Djelantik (Jurnal Administrasi Publik, 2008)
"Corruption is often at the very root of why governments don't work.... It weakens the systems and distorts the markets. In the end, governments and citizens will pay a price, in lower incomes, lower investment and more volatile economic swings. But when governments do work--when they tackle corruption and improve their rule of of law--they can raise their national incomes by as much as four times."Paul Wolfowitz, http://china.org.cn/english/MATERIAL/165357.htmKeyword: corruption, good government, anti-corruption policy